2020
DOI: 10.1021/acssuschemeng.0c05989
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing TEMPO-Oxidized Cellulose Fiber Morphology: New Insights into Optimization of the Oxidation Process and Nanocellulose Dispersion Quality

Abstract: High-definition automated optical analysis was used to observe the morphological changes of bleached hardwood dissolving pulp during oxidation mediated by (2,2,6,6-tetramethylpiperidn-1-yl)­oxyl (TEMPO). The effects of TEMPO treatment kinetics on fiber morphology and fibrillation degree at a constant reagent loading were studied. The pulp underwent significant swelling, and carboxyl groups were introduced in which the fiber cell walls loosened, which contributed to fibrillation and subsequently nanocellulose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 47 publications
3
41
0
3
Order By: Relevance
“…The main benefit of pretreatment is to reduce the energy demand and to avoid clogging in the subsequent treatments, but pretreatments can have a notable effect on CNF characteristics and behavior. Severe pretreatment affects the integrity of the fibers and generates a large amount of fines, which is a potential problem for the subsequent processing stages (Levanič et al 2020). Several researchers have demonstrated that CNFs of very high aspect ratio, which demand a high energy consumption, have only marginal increased mechanical strength compared to less fibrillated products (Ang et al 2019;Balea et al 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…The main benefit of pretreatment is to reduce the energy demand and to avoid clogging in the subsequent treatments, but pretreatments can have a notable effect on CNF characteristics and behavior. Severe pretreatment affects the integrity of the fibers and generates a large amount of fines, which is a potential problem for the subsequent processing stages (Levanič et al 2020). Several researchers have demonstrated that CNFs of very high aspect ratio, which demand a high energy consumption, have only marginal increased mechanical strength compared to less fibrillated products (Ang et al 2019;Balea et al 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of hemicellulose in this pulp could suppose that this loss of material could also be affected by the loss of oxidized hemicellulose. [ 28 ] This high number of effects could be responsible for the fluctuations found in the recovery rate of eucalyptus CNF, which varied in a high proportion from one cycle to the other.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation process, using various chemicals, including metaperiodate, hypochlorite, dichromate, nitrogen dioxide, or TEMPO (2,2,6,6-tetramethylpiperidn-1-yl)oxyl) [ 239 , 240 , 241 , 242 , 243 ], makes cellulose materials more vulnerable to hydrolysis and therefore potentially degradable by the human body. The only impediment of this process is that it can significantly alter the structure of cellulose, disturbing the unique, medically desirable properties of cellulose, such as its high tensile strength and conformability.…”
Section: Toxicological Evaluation and Potential Limitations Of Ncs-based Materialsmentioning
confidence: 99%